2014
DOI: 10.1136/annrheumdis-2013-203854
|View full text |Cite
|
Sign up to set email alerts
|

Degree of bone marrow oedema in sacroiliac joints of patients with axial spondyloarthritis is linked to gut inflammation and male sex: results from the GIANT cohort

Abstract: Higher degrees of BMO were observed in patients showing chronic gut inflammation. These data solidify a link between mucosal inflammation and progressive disease in axial SpA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 21 publications
4
79
1
3
Order By: Relevance
“…The prevalence of gut inflammation was similar in the group with AS and the group with nonradiographic axial spondyloarthritis. Another characteristic of this cohort is an association between gut inflammation and the severity of sacroiliac MRI bone edema in males with axial spondyloarthritis [5]. This research group also reported that the gut mucosa of patients with gut inflammation exhibited increased mucous-membrane vascularity, together with increased expression of VEGF, VCAM-1, and placental growth factor [6], which create an environment conducive to immune cell traffic.…”
Section: Associations Linking Gut Inflammation To Spondyloarthritismentioning
confidence: 92%
“…The prevalence of gut inflammation was similar in the group with AS and the group with nonradiographic axial spondyloarthritis. Another characteristic of this cohort is an association between gut inflammation and the severity of sacroiliac MRI bone edema in males with axial spondyloarthritis [5]. This research group also reported that the gut mucosa of patients with gut inflammation exhibited increased mucous-membrane vascularity, together with increased expression of VEGF, VCAM-1, and placental growth factor [6], which create an environment conducive to immune cell traffic.…”
Section: Associations Linking Gut Inflammation To Spondyloarthritismentioning
confidence: 92%
“…Involvement of the gastrointestinal tract in the pathogenesis of SpA is strongly suggested because subclinical gut inflammation is present in up to 60% of patients with SpA [22]. SpA-associated gut inflammation has been demonstrated to be an important prognostic factor in SpA because it is associated with more extensive bone marrow edema of the sacroiliac joints and a higher risk of progression to AS [23] and of developing Crohn's disease (CD) [24].…”
Section: Spondyloarthritismentioning
confidence: 99%
“…La prévalence de l'inflammation intestinale était comparable entre spondylarthrite ankylosante et spondyloarthrite axiale non radiographique. D'autre part, les auteurs ont également montré sur cette cohorte un lien entre inflammation digestive et le degré d'oedème sacro-iliaque en IRM chez les sujets de sexe masculin atteints de spondyloarthrite axiale [5]. Enfin, cette équipe a observé dans la muqueuse digestive des patients avec inflammation une augmentation de l'expression de VEGF, de la vascularisation muqueuse et de l'expression de VCAM-1 et du facteur de croissance placentaire [6], favorisant ainsi un environnement propice au trafic (circulation) des cellules immunes.…”
Section: Relations Entre Inflammation Intestinale Et Spondyloarthriteunclassified